PENGARUH ATRIBUT-ATRIBUT KUALITAS AUDIT TERHADAP KEPUASAN KLIEN (Studi Empiris Pada Perusahaan Perbankan di Kota Medan) - Jadongan Sijabat (LPPM Universitas HKBP Nommensen, 2020)
This research is a study about attributes of audit quality. The purpose of this research is to re-examine the effect of attributes of audit quality to client satisfaction as Bhen et al (1997). This research conducted with survey on perception of financial managers or controller, that distributed by mail survey to 100 financial manager of banking in Medan City. Unit analysis are the financial managers or controller of banking. There are fifty five questionaires (55%) received and analyzed by Ordinari Least Square supported by SPSS 10.00 program. The results showed that some of attributes of audit quality effected client satisfaction. The results showed that there were some different result between this study and Bhen et al. (1997).